Pollution inequality 50 years after the Clean Air Act: the need for hyperlocal data and action. (1st July 2021) - Zhang, Yang; Smith, Steve J; Bell, Michelle; Mueller, Amy; Eckelman, Matthew; Wylie, Sara; Sweet, Elizabeth L; Chen, Ping; Niemeier, Deb A
Abstract: Effective solutions require integration of improved data, technology innovations, community engagement, and environmental justice.